A dark page in history : the Nanjing Massacre and post-massacre social conditions recorded in British diplomatic dispatches, admiralty documents, and U.S. naval intelligence reports /: the Nanjing Massacre and post-massacre social conditions recorded in British diplomatic dispatches, admiralty documents, and U.S. naval intelligence reports. (2019) - Lu, Suping
No abstract available